Comparing Asian politics India, China, and Japan - Charlton, Sue Ellen M. (Westview Press, 2014)
"Comparing Asian Politics presents an invaluable comparative examination of politics and government in three Asian nations: India, China, and Japan. The author elucidates the links between politics and each nation's distinctive cultural and historical contexts and demonstrates the intermingling and grafting of Asian traditions with the influence of Western values and institutions. National identity, political cohesion, and socioeconomic change emerge as central to how politics has developed in each nation-state. Also included are focus boxes on political and social issues in other important countries in Asia. The book provides insight into topics such as the significance of constitutions in the political process; the parliamentary system in Asia; the regionalization of politics and the importance of levels of government; the decay of one-party rule; the links between development and democratization; and the impact of globalization. This essential text not only illuminates the politics of India, China, and Japan in relation to one another, it also suggests to readers how their own experience of politics can be informed by understanding the politics and government of these three Asian nations. In this new edition, the author includes a discussion on the recent political changes in China and the election of Xi Jinping in early 2013, the devastating earthquake and tsunami that hit Japan in 2011, and the recent elections in India".